Enseignement et apprentissage de l’algèbre abstraite à l’Université : vers un paradigme du questionnement du monde - Hausberger, Thomas (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Abstract It is discussed in this article what may be the study of Abstract Algebra at University in the paradigm of “questioning the world”. This leads to the distinction between “top-down” and “bottom-up” approaches of the teaching of algebraic structures and the consideration of particular praxeologies in abstract algebra that are called “structuralist praxeologies”. Building on this Reference Epistemological Model, it is argued that questioning the world in the context of abstract algebra should be about setting up a Study and Research Path which presents a good vitality of the fundamental particular-general and objects-structures dialectics. This point of view is illustrated on an example which consists in an innovative use of a transcript of a discussion on a forum; the pertinence and difficulties of such an approach are discussed. Résumé Nous discutons dans cet article ce que pourrait être l’étude de l’algèbre abstraite à l’Université dans le paradigme du questionnement du monde. Ceci nous amène à distinguer des approches « top-down » et « bottom-up » de l’enseignement des structures algébriques et à considérer des praxéologies particulières en algèbre abstraite que nous nommons « praxéologies structuralistes ». À partir de notre modèle épistémologique de référence, nous soutenons le point de vue qu’un questionnement du monde en algèbre abstraite doit s’apparenter à un parcours d’étude et de recherche qui présente une bonne vitalité des dialectiques fondamentales particulier-général et objets-structures. Nous illustrons ce point de vue sur un exemple présentant un usage innovant d’une retranscription d’échanges sur un forum et nous discutons la pertinence et les difficultés d’une telle approche.